The Anthem Companion to Norbert Elias - Law, Alex; Mennell, Stephen (Anthem companions to sociology., 2023)
The book brings together authoritative chapters by leading experts in the sociology of Elias. It charts Elias's ambition to create an integrative sociological framework across a wide range of studies and assesses its continuing relevance for addressing significant issues facing sociology today.